Weather risk management in the agricultural sector of Poland and in the world - Dorota Michalak (Comparative Economic Research. Central and Eastern Europe, 2015)
Farming is an activity which is heavily exposed to risk. Farmers have to deal daily with the change of weather, crops, and prices, resulting not only in fluctuations in income, but also in the need to incur emergency expenses. The purpose of this paper is to analyse the available catastrophic insurance dedicated to the agriculture sector, with particular emphasis on compulsory insurance and with a comparison of the insurance systems of other countries and the Polish system. I also examine the level of awareness of Polish entrepreneurs in the agricultural industry of the impact of weather conditions on the business. The methodology used to answer the research question was the CAWI survey and market research. Despite the mandatory insurance of the selected risks, farmers still do not see the necessity to purchase insurance. The very design of the instrument raises questions, especially about the enforcement system for compliance with the insurance obligation and the type of risk being insured. The low awareness of the impact of weather on agricultural business and the possibility to protect the farm and benefits via the undertaken insurance activities is an undoubted problem in the development of insurance instruments on the market to protect the agricultural sector against adverse weather conditions. While one can see some similarities when comparing agricultural insurance schemes in different countries, nonetheless it is clear that these systems are significantly different from each other. This difference is justified, as is not possible to create a single coherent system which would take into account the economic, social, and cultural differences. Viewed against the background of insurance schemes operating in other countries, the Polish system looks disadvantageous. Given the rapid increase in the number of extreme weather phenomena and their increasing scale there is an urgent need for reforms.
Keywords: 330; agricultural insurance; compulsory insurance; weather derivatives; catastrophic weather risk management